Comparison of Chemical Compounds and Antioxidant and Antibacterial Properties of Various Satureja Species Growing Wild in Iran - M Ghorbanpour; J Hadian; M Hatami; H Salehi-Arjomand; A Aliahmadi (Institue of Medicinal Plants, ACECR, 2016)
Background: Many members of the genus Satureja L. (Lamiaceae) have interesting pharmacological and biological properties. Objective: In this research, major essential oil (EO) compositions, rosmarinic acid (RA) content, and antioxidant and antibacterial properties of the leaf extracts of nine Satureja species (S. bachtiarica, S. mutica, S. sahandica, S. macrantha, S. atropatana, S. edmondi, S. spicigera, S. isophylla and S. intermedia) were assessed. Methods: The chemical composition of EO was determined using Gas Chromatography (GC) and Gas Chromatography/Mass Spectrometry (GC-MS) analysis. RA content of the extract was detected using a High-Performance Thin-Layer Chromatography (HPTLC) method, and the 2,2-diphenyl-2-picrylhydracyl hydrate (DPPH) radical scavenging procedure was used to study of antioxidant capacity. Results: According to the analytical results, EO of the most samples were mainly composed of p-cymene, γ-terpinene, thymol, and carvacrol. There was a wide variability for RA content among the studied species ranging from 0.03 mg g-1 RA (S. sahandica) to 1.11 mg g-1 RA (S. isophylla). The lowest IC50 in the radical scavenging assay was shown by S. sahandica extracts as compared to the other samples. This activity was followed by S. spicigera and S. edmondi. The minimum inhibitory concentration (MIC) varied from 0.06 to 32 mg ml-1, however, the minimum bactericidal concentration (MBC) value differed from 0.06 to ˃64 mg ml-1. Moreover, S. sahandica revealed the lowest inhibitory activity against all microorganisms tested particularly on E. coli. Conclusion: In conclusion, the extracts of certain Satureja species have the potential to be considered as alternatives for synthetic food preservatives and antibiotics.